Handover Strategies in Beacon-Enabled Mobile Sensor Network. (4th March 2014) - Sthapit, Pranesh; Pyun, Jae-Young
IEEE 802.15.4 has become the de facto standard in many areas of wireless sensor network (WSN) such as body area networks, industrial automation, and healthcare domains. In many WSN applications, the sensor nodes could be mobile, and indoor communications are limited in terms of signal propagation. Therefore, a large number of access points need to be deployed to cover large areas. To maintain the sensor connectivity, sensor node should frequently change the serving access point by performing a mechanism known as a handover. We observed that the amount of time required for the association process is the key reason IEEE 802.15.4 is unable to handle the mobility. In this paper, we show what is required for node mobility support and propose three strategies for the support. First, the proactive algorithm is developed to anticipate the future link breakage. Second, a new greedy scanning technique is presented, which prevents nodes from scanning multiple channels. Third, the coordinator selection algorithm is developed which chooses the best coordinator that gives the longest connectivity time reducing the handover frequency. Experimental results have verified that our schemes work well in the mobile sensor network environment.